SOHO comets: 20 years and 3000 objects later. (29th May 2017) - Battams, Karl; Knight, Matthew M.
Abstract : We present a summary of the more than 3000 sungrazing and near-Sun comets discovered in coronagraph images returned by the Solar and Heliospheric Observatory (SOHO), since its launch in December 1995. We address each of the four main populations of objects observed by SOHO: Kreutz (sungrazing) group, Meyer group, Marsden and Kracht (96P-family) group and non-group comets. Discussions for each group include basic properties, discovery statistics and morphological appearance. In addition to updating the community on the status of the discoveries by SOHO, we also show that the rate of discovery of Kreutz sungrazers has probably remained static since approximately 2003 and we report on the first likely fragmentation pair observed within the Meyer group. This article is part of the themed issue 'Cometary science after Rosetta'.